2020
DOI: 10.3126/kumj.v18i3.49225
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pneumothorax: Follow up Treatment Outcome in a Tertiary Care Center of Eastern Nepal

Abstract: Background Spontaneous pneumothorax is not an uncommon medical emergency in pulmonary practice. Related data are not available in our setting. In emergency departments, clinical presentation is often confused with other cardiopulmonary problems. Follow up outcome is important for better patient care. Objective To study clinical profile and outcome after non surgical intervention in a tertiary care center. Method This was a prospective observational study carried out in Nobel Medical College, Biratn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Most of the studies were either of low (n ¼ 13) or moderate (n ¼ 12) quality, with two classed as high quality. Some studies reported on more than one condition, with the major diseases identified being: COPD (22 studies), 31,32,[34][35][36][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] asthma (8 studies), 20,32,36,37,49,[52][53][54] bronchiectasis (2 studies and as a co-morbidity in one), 30,40,52 restrictive lung diseases (3 studies), 49,51,52 and 'chronic bronchitis' (1 study). 29 Symptoms reported included chronic cough, phlegm or sputum production, breathlessness or shortness of breath, chest tightness, wheezing, dyspnoea and sore throat.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the studies were either of low (n ¼ 13) or moderate (n ¼ 12) quality, with two classed as high quality. Some studies reported on more than one condition, with the major diseases identified being: COPD (22 studies), 31,32,[34][35][36][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] asthma (8 studies), 20,32,36,37,49,[52][53][54] bronchiectasis (2 studies and as a co-morbidity in one), 30,40,52 restrictive lung diseases (3 studies), 49,51,52 and 'chronic bronchitis' (1 study). 29 Symptoms reported included chronic cough, phlegm or sputum production, breathlessness or shortness of breath, chest tightness, wheezing, dyspnoea and sore throat.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Reporting included presence of pulmonary arterial hypertension 30 and cor pulmonale. 29,30,35,51,52 Lung function was reported in seven studies, 29,32,33,38,47,48,51 and data presented across different spirometric measures, with one reporting proportions only of patients categorised as 'normal', 'obstruction' and 'restriction'. 51…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations